Sociologie du travail et critique du temps industriel - Jens Thoemmes (Temporalités)
The sociology of work and labor developed a particular viewpoint on the analysis of social times. The objective of this article is to show how a criticism of a unique and unifying industrial time progressively grew up. Such criticism leans on three elements: the multiplicity of social times linked to the occupational activity, the disintegrating nature of work in the manufacturing process and the emergence of leisure-time. This point of view was elaborated by the sociology of work in France after 1945, notably by Georges Friedmann, Pierre Naville and William Grossin. Before approaching this period we question the moment of the foundation of sociology. By mobilizing little known research by Max Weber on the manufacturing process, we shall see in what way he was a precursor of the analysis of diversified attitudes regarding time by individuals and groups.